2011
DOI: 10.1371/journal.pone.0026277
|View full text |Cite
|
Sign up to set email alerts
|

A New Methodology to Associate SNPs with Human Diseases According to Their Pathway Related Context

Abstract: Genome-wide association studies (GWAS) with hundreds of żthousands of single nucleotide polymorphisms (SNPs) are popular strategies to reveal the genetic basis of human complex diseases. Despite many successes of GWAS, it is well recognized that new analytical approaches have to be integrated to achieve their full potential. Starting with a list of SNPs, found to be associated with disease in GWAS, here we propose a novel methodology to devise functionally important KEGG pathways through the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 70 publications
(117 reference statements)
0
46
0
Order By: Relevance
“…8,19,20,[26][27][28] PANOGA is publicly available at http://panoga.sabanciuniv.edu. In this study, we further improved PANOGA to identify SNP-targeted pathways with the genes responsible for BD susceptibility.…”
Section: Network and Pathway Oriented Gwas Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…8,19,20,[26][27][28] PANOGA is publicly available at http://panoga.sabanciuniv.edu. In this study, we further improved PANOGA to identify SNP-targeted pathways with the genes responsible for BD susceptibility.…”
Section: Network and Pathway Oriented Gwas Analysismentioning
confidence: 99%
“…In this regard, pathway-based approaches to GWAS may be more helpful in a search for multiple genes involved in the same biological pathway, where the common variations in each of these genes have little correlation with disease risk. [8][9][10][11][12][13][14] It has been observed that genes that have aberrations associated with a given complex disease tend to be part of the same subnetwork of the overall protein-protein interaction (PPI) network. 15,16 Hence, to be able to explain the connections between genotypic and phenotypic data, perturbed network modules need to be detected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only three studies have investigated the use of similarity of patient-specific genomic information for classification purposes (Bakir-Gungor and Sezerman, 2011;Hofree et al, 2013;Wang et al, 2014). However, these studies use gene-centric reference to map SNPs to pathways and gene interaction networks, the idea we have also independently explored (https://github.com/ mdozmorov/PathwayRunner).…”
Section: Discussionmentioning
confidence: 99%